Metabolic conjugation reduces in vitro toxicity of the flavonoid nevadensin. (June 2022) - Müller, Lena; Keuter, Lucas; Bücksteeg, David; Uebel, Thomas; Wilken, Markus; Schürmann, Lina; Behrens, Matthias; Humpf, Hans-Ulrich; Esselen, Melanie
Abstract: The present study focuses on the association between metabolic capacity and toxicity of the natural occurring flavonoid nevadensin in vitro . Human colon (HT29), liver (HepG2) and bone marrow (KG1) carcinoma cells were used and strong cell line dependent differences in toxic effect strength were found. HepG2 and KG1 cells were more sensitive against nevadensin treatment in comparison to HT29 cells. High resolution mass spectrometry experiments showed that nevadensin is rapidly glucuronidated in HT29 cells, whereas KG1 cells do not metabolize nevadensin, thus glucuronidation was supposed to be a crucial metabolic pathway in vitro . To proof this suggestion, nevadensin glucuronides were isolated from pig liver microsomes und structurally elucidated via NMR spectroscopy. In HepG2 cells a cellular enrichment of nevadensin itself as well as nevadensin-7- O -glucuronide was determined by tandem mass spectrometry. A proteomic screening of uridine 5′-diphospho (UDP)-glucuronosyltransferase (UGT) in HT29 and HepG2 cells provided first hints that the isoforms UGT1A6 and UGT1A1 are responsible for nevadensin glucuronidation. Additionally, nevadensin was found to be a potent SULT inhibitor in HepG2 cells. In sum, the present study clearly illustrates the importance of obtaining detailed information about metabolic competence of cell lines which should be considered in the evaluation of toxic endpoints. Highlights: Metabolic capacity is clearly related to toxic effects of nevadensin. Identification of nevadensin phase II metabolites in cell lines. Isolation and structure elucidation of nevadensin glucuronides. Proteomic approach supports selected uridine 5′-diphospho (UDP)-glucuronosyltransferase contribution. Nevadensin is characterized as a potent cellular SULT inhibitor.